2019
DOI: 10.1002/phar.2342
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Weight‐Loss Pharmacotherapy in Persons Living with HIV: A Review of the Literature and Potential Drug‐Drug Interactions with Antiretroviral Therapy

Abstract: The prevalence of obesity among persons living with human immunodeficiency virus (HIV) has increased significantly and may be linked to the use of antiretroviral therapy. Although weight‐loss medications approved by the U.S. Food and Drug Administration are recommended as an adjunct to diet and exercise to treat obesity in the general population, little is known about the safety and efficacy of these drugs specifically in persons living with HIV. We review the available evidence regarding the effective use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Current treatments of obesity mainly include behavioral therapy, drugs, and surgery, with the latter two modalities especially possessing a large number of side effects. As one case study reported, use of certain weight-loss pharmacotherapies may affect control of HIV viral load [ 10 ]. Since obesity greatly impacts people's life and work habits and currently has limited treatment options available, researching safe and effective interventions with low rates of adverse reactions is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…Current treatments of obesity mainly include behavioral therapy, drugs, and surgery, with the latter two modalities especially possessing a large number of side effects. As one case study reported, use of certain weight-loss pharmacotherapies may affect control of HIV viral load [ 10 ]. Since obesity greatly impacts people's life and work habits and currently has limited treatment options available, researching safe and effective interventions with low rates of adverse reactions is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…First, a high pMRCI is a measure of higher complexity, which makes it troublesome for the patient to take medications, thus leading to lower adherence. Second, a more complex medication regimen has the potential for more drug‐drug interactions, which could theoretically impact TFV‐DP concentrations; however, interactions of this magnitude are not likely 34,35 . Third, a more complex medication regimen is a marker for more comorbidities, which could influence drug concentrations, as was previously observed in this cohort in PWH and diabetes mellitus 36 .…”
Section: Discussionmentioning
confidence: 70%
“…Orlistat was recommended to avoid concomitant use with most available ART drugs, except injectable entry inhibitors, and naltrexone/bupropion also has serious drug-drug interactions with NNRTIs, PIs, and INSTIs [ 78 ]. Liraglutide has no clinically relevant interactions with NRTIs, INSTIs, and entry inhibitors, but it has a drug-drug interaction with ritonavir and PIs.…”
Section: Management Of Weight To Control Metsmentioning
confidence: 99%
“…Therefore, it is not contraindicated but clinical monitoring is recommended. Atazanavir and rilpivirine should be administered 4 h before liraglutide due to the potential for inhibition of gastric secretion, resulting in decreased concentrations of atazanavir and rilpivirine [ 78 ]. Pentermine/topiramate also has some drug interactions with antiretroviral agents, such as ritonavir or cobicistat (moderate CYP2D6 inhibitor) and efavirenz (CNS depression effect); therefore, it should be administered under close clinical monitoring because of the potential for increased concentrations of phentermine ( http://www.uptodate.com .…”
Section: Management Of Weight To Control Metsmentioning
confidence: 99%